The use, publication and future directions of immunocytochemistry in veterinary medicine: a consensus of the Oncology‐Pathology Working Group. (22nd March 2016) - Priest, H. L.; Hume, K. R.; Killick, D.; Kozicki, A.; Rizzo, V. L.; Seelig, D.; Snyder, L. A.; Springer, N. L.; Wright, Z. M.; Robat, C.
Abstract: One of the primary objectives of the Oncology Pathology Working Group (OPWG), a joint initiative of the Veterinary Cancer Society and the American College of Veterinary Pathologists, is for oncologists and pathologists to collaboratively generate consensus documents to standardize aspects of and provide guidelines for oncologic pathology. Consensus is established through review of relevant peer‐reviewed literature relative to a subgroup's particular focus. In this document, the authors provide descriptions of the literature reviewed, the review process, and a summary of the information gathered on immunocytochemistry. The intent of this publication is to help educate practitioners and pathologists on the process of immunocytochemistry and to provide a guide for the use of this technique in veterinary medicine. This document represents the opinions of the working group and the authors and does not constitute a formal endorsement by the American College of Veterinary Pathologists or the Veterinary Cancer Society.